ʿAbd al-Karīm al-Fakkūn’s corrections in his Naẓm al-Durar fī Sharḥ al-Mukhtaṣar of Ibn al-Musabbiḥ’sʿUmdah al-Bayān - hamida, rafik (Journal of Social Sciences and Humanities, 2020)
This article focuses on corrections of Shaykh al-Islam ʿAbd al-Karīm al-Fakkūn in his book Naẓm al-DurarfīSharḥ al-Mukhtaṣar on the Jurist Ibn al-Musabbiḥ’s work ʿUmdah al-Bayān، in particular by collating all suchcorrections. These corrections have been thematically categorising according to methodology، miscellaneous issues. I have placed underneath the study the text of ʿUmdah al-Bayān and Shaykh al-Fakkūn’s critique of it. This is followed up with a comparative analysis utilising the most authoritative sources of both authors and with contributions from the present author. This study illustrates that these corrections pertain to jurisprudential issues given the subject of both books. Notwithstanding that، there are other critical issues pertaining to methodology، nomenclature، including grammar. Given that these corrections cannot be completely appreciated without a methodological study، I have described al-Fakkūn’s method in his corrections، and how they contrast from being soft and gentle to harsh and biased. This I have reiterated by recourse to the foundations upon which al-Fakkūn has built his polemic. Evidently، whenever the need arises، he relies on authoritative works and recognised imams of the field with much prudence and diligence. Finally the study culminates in shedding light on his position on Ibn al-Musabbiḥ، which ostensibly indicates that there are factors influencing al-Fakkūn’s critical disposition، such as not considering the author of ʿUmdah an independent jurist. Consequently this bias prevented him to view Ibn al-Musabbiḥ as competent in authoring in this field. The results of this study indicate that despite Shaykh al-Fakkūn’s critical disposition، pedantic scholarship and his sharp approach، most of his corrections appear to be correct.